556 Axillary lymphadenectomy vs. sentinel node biopsy for early-stage clinically node-negative breast cancer: a systematic review and meta-analysis. (4th December 2020) - Petousis, Stamatios; Christidis, Panagiotis; Margioula-Siarkou, Chrysoula; Liberis, Anastasios; Vavouldis, Eleftherios; Margioula-Siarkou, Georgia; Papanikolaou, Alexios; Mavromatidis, George; Dinas, Konstantinos
Abstract : Introduction/Background: Axillary lymph node dissection had been for years the gold standard for surgical staging and locoregional control of axilla in early-stage breast cancer patients. However, sentinel node biopsy has been placed in early 1990s as an effective alternative method of surgical staging. Main objective of the study is to compare oncological and survival outcomes between systematic axillary lymph node dissection (ALND) vs sentinel lymph node and axillary lymphadenectomy only if sentinel positive (SLN ± ALND) in early-stage, clinically node-negative breast cancer patients. Methodology: A systematic review and meta-analysis adhered to PRISMA guidelines was performed. Included studies were prospective randomized controlled trials (RCTs) comparing survival outcomes of ALND vs. SLN ± ALND in early-stage, node-negative breast cancer patients. Patients enrolled were only those with tumor size lower than 4 cm, clinically negative nodes and treated with breast-conservative surgery. Primary outcomes were locoregional recurrence, overall death and cancer-related death. Results: There were four studies included in the analysis, enrolling overall 2, 982 patients, of which 1, 494 in ALND arm and 1, 488 in the SLN ± ALND arm. No statistically significant difference was observed in locoregional recurrence, breast cancer-related death and overall death. Locoregional recurrence was observed in 2.8% (ALND) vs. 4.1% (SLND± ALND), (RR: 0.69, 95% CI: 0.20–2.30). Overall death rate was 7.0% vs. 6.8% respectively, (RR:1.00, 95% CI: 0.73–1.39, I2=28.7%). Breast cancer-related death was 3.6% vs.3.5% respectively (SLN ± ALND), (RR: 1.11, 95% CI: 0.70–1.78, I2=0%). No statistically significant difference was observed in any of secondary study outcomes. Conclusion: Systematic axillary lymphadenectomy provides no survival and oncological benefit compared with sentinel lymph node dissection for early-stage clinically node-negative breast cancer patients. Disclosures: Authors report no conflict of interest.